Long-term prognosis of life in patients with cerebrovascular accident: the role of diabetes mellitus (according to the REGION-M registry outpatient follow-up phase) - V. P. Voronina; A. V. Zagrebelny; Yu. V. Lukina; S. N. Tolpygina; N. P. Kutishenko; M. I. Chernysheva; M. M. Lukyanov; N. A. Dmitrieva; O. V. Lerman; S. Yu. Martsevich; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2024)
Aim. To study the long-term prognosis of patients’ life who have suffered cerebrovascular accident (CVA), and to determine the role of diabetes mellitus (DM) as a possible negative prognostic factor, according to the outpatient follow-up stage in the REGION-M registry.Material and methods. The outpatient part of the REGION-M registry included 684 patients assigned to the Moscow City Polyclinic No. 64, discharged from the hospital in the period from 01.01.2012 to 30.04.2017 with a confirmed diagnosis of CVA, of which 122 patients (17.8%) were diagnosed with DM. The polyclinic stage included three observation points: 2017, 2020, and 2022. Data on the life status of all patients were obtained by telephone survey, if it was impossible to establish contact with the patient or his relatives, a unified medical information and analytical system was used to determine the life status of patients. The study patients were observed on an outpatient basis for more than 5 years (ME 1958 (751; 2555) days), the primary endpoint was death from any cause.Results. Information about the life status was obtained for all 684 patients. By the end of the observation, 415 cohort members had died, and 269 were alive. The average age of patients with DM was significantly higher than that of patients without DM: 71.5±10.9 years vs 68.0±14.7 years (p<0.05). The proportion of women in the cohort of DM patients was significantly higher than in the cohort of patients without DM: 72.1% vs 55.2% (p<0.05). Patients with DM were statistically significantly more likely to have a history of comorbid diseases (coronary heart disease, myocardial infarction, arterial hypertension, kidney disease and chronic lung disease, chronic heart failure). Obesity occurs with the same frequency in patients with and without DM. The studied groups of patients did not differ in types of CVA (transient ischemic attack, ischemic, hemorrhagic stroke). According to Cox Proportional Hazards Regression Analysis at the outpatient stage of follow-up, no significant negative effect of DM on patients’ mortality with CVA was confirmed (relative risk =1.239 (95% CI: 0.975; 1.574), p=0.079).Conclusion. In the long-term follow-up of patients with CVA, there was no statistically significant adverse effect of DM on long-term survival.